Postoperative Pulmonary Complications in Surgical Patients, Risk Factors, Prevention Strategies, and Clinical Outcomes - Nawaz Ali Dal, Jamshed Bashir, Tanveer Sadiq Ch, Abdul Waheed, Muhammad Ikram Ul Haq, Salman Ahmed Niaz Mangrio, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: PPCs are a major cause of morbidity and mortality in surgical patients, causing prolonged hospital stays, ICU admissions, and increased healthcare costs. The objective of this study was to assess the incidence, risk factors, and clinical outcomes of PPCs in surgical patients admitted to tertiary care hospitals in Pakistan. Methods: A prospective observational study was conducted for 12 months on n=70 patients having major elective and emergency surgery. Demographics, comorbidities, ventilation parameters, and pulmonary complications were data collected preoperatively, intraoperatively, and postoperatively. C-reactive protein (CRP), procalcitonin, arterial oxygen saturation (SpO₂), lactate levels, and the neutrophil-to-lymphocyte ratio (NLR) were determined as biomarkers. SPSS version 26.0 was used for statistical analysis, and p < 0.05 was taken as significant. Results: Pneumonia was the most common (50%) and occurred in 42.9% of patients who had PPCs. PPC patients had longer hospital stays (11.8 vs. 7.1 days, p = 0.002), higher ICU admissions (50% vs. 12%, p = 0.003), and 30-day mortality (18% vs. 8%), but not statistically significantly (p = 0.056). Elevations of biomarkers in PPC patients (p < 0.001) suggested an inflammatory role in PPC development. Conclusion: Surgical outcomes and hospital resource utilization are significantly influenced by PPCs. Perioperative interventions might be targeted given biomarkers as early indicators of PPC risk. Future research should move forward to integrate biomarkers into risk models and to optimize pulmonary care strategies to improve outcomes. Keywords: Postoperative pulmonary complications, surgery, pneumonia, ICU admission, biomarker analysis, pulmonary risk assessment, surgical outcomes.